Counselling attributes for online game design model - Okpakhomhe, Ididi Italumeh (2018)
In recent times, online game play has become a food for thought to concerned individuals, researchers and authorities of various countries due to its excessive and addictive usage. Although, various government have taken certain measures such as shutting down internet cafe at certain hours of the day, censoring the most brutal, offensive and aggressive sections of certain games before they are released. Researchers have advised developers on ways of limiting harm on players by suggesting design changes on time limit. Furthermore, researchers have also suggested that online game distributors ought to make available appropriate referral services. The impart of the above are yet to make any remarkable impact on players. In this research, a Counselling Attributes Model (CAM) is proposed as a control measure in minimizing online game effect on Cognitive Behavioural Therapy (CBT) components as a key to minimizing excessive play and core addictive gaming habits. Campaign messages designed as informative in nature while appraisal messages designed as selfappraisal messaging from the proposed model are integrated in the game to stream at the bottom centre of the gaming screen. While informative messages are streamed at every two minutes, self-appraisal messages are streamed at faster interval at every one minute in red colour, capital letter and with annoying sounds, are determined with optimistic believe to make positive impact on player's thoughts, emotions and behaviour towards gaming. The proposed model is to show or remind players about the negative impact of excessive and addictive gaming habits, as well as suggesting possible reductive solutions through message streaming. A total of 132 participants took part in the experiment which was conducted based on between subject of 66 experimental and 66 control groups by administering the game integrated with CAM on the experimental group and the game without CAM on the control group. Results generally reveal that the experimental group received significant impact from the game with CAM as compared to the control group without CAM. The experimental group also shows significant effect on CBT component as well as excessive play criteria (Salience, Tolerance and Mood modification) and core addiction criteria (Withdrawal, Relapse, Conflicts and Problems).